Analisis Laporan Arus Kas Untuk Menilai Kinerja Keuangan PT Telekomunikasi Indonesia Di Bursa Efek Indonesia - simanjuntak, sara cristin; Jefri, Riny (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2024)
In this research, the author intends to examine the financial performance of PT Telekomunikasi Indonesia by calculating ratio analysis which includes the operating cash flow ratio, total debt ratio, and the ratio of cash flow to the company's net profit. The author used a qualitative descriptive research method in this research. . The object of this research is the financial reports for the last five years. Through this research, the author obtained results, namely a decrease in several ratios in 2023 which was caused by several factors.